2021
DOI: 10.1186/s12887-021-02819-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and influencing risk factors of eczema among preschool children in Urumqi city: a cross-sectional survey

Abstract: Background Eczema is a chronic inflammatory disease associated with impaired quality of life. We identified indoor environmental risk factors, to provide strong evidence for the prevention and control of eczema in preschool children. Methods Using a cross-sectional study with stratified random cluster sampling, we conducted a self-administered questionnaire survey among 8153 parents of children aged 2–8 years in 60 kindergartens in six districts of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
4
13
0
1
Order By: Relevance
“…However, the terms "atopic eczema" and "atopic dermatitis" are still frequently employed to describe poorly defined inflammatory skin conditions with surface changes, a preference for flexures, and a family or personal history of allergic rhinitis or asthma [2]. The itching associated with eczema can disrupt children's sleep patterns and, in more severe cases, potentially impair physical and mental development [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the terms "atopic eczema" and "atopic dermatitis" are still frequently employed to describe poorly defined inflammatory skin conditions with surface changes, a preference for flexures, and a family or personal history of allergic rhinitis or asthma [2]. The itching associated with eczema can disrupt children's sleep patterns and, in more severe cases, potentially impair physical and mental development [3].…”
Section: Introductionmentioning
confidence: 99%
“…The causes of this large variance in eczema prevalence are not known. Eczema is a complex skin condition that can vary in severity due to genetics, environmental factors, and cultural exposures [3,6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Although it is greatly influenced by genetic factors and environmental exposure, its pathogenesis is still not fully understood. [8][9][10][11] Study reported that its prevalence has increased around the world. [12][13][14] If such condition can not be treated fairly well, they may result in food allergies, wheezing, asthma, allergic rhinitis, and psychological and behavioral disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Eczema produces itching, which can disrupt sleep in children and, in extreme cases, hinder physical and mental development. Eczema can develop into asthma or rhinitis, and the management of eczema and its aggravating factors can be costly for the patient (6). Allergic rhinitis is an immunoglobulin Emediated disease caused by allergen exposure to the nasal mucosa.…”
Section: Introductionmentioning
confidence: 99%